(3GdLfi GdOGfj aj MQha GdeYGfjs - (3GdMSf Hf bGSe Hf YHO Gddg GdeQGOj GdeUQj, HOQ GdOjf CHh eMeO, GHf Ge bGSe , J (B749 (3g` s ((3MSf Hf YeQ Hf HcQ Hf Gdbhfhj s)
(3ChdgG (B:s
(3hCeG GdeNJU HGdaYd adG jNdh CjVkG ef Cf jfRd efg efRdI GdLRA ChdkG hEf de jfRd efg efRdI GdLRA aMbg Cf jYed s
(3BNQgG (B:s
(3hEfeG CgedJ PcQgG gfGc dTgQJgG hZQGHI Gdbhd HMQaJjgG hddcdGe YdjgG ehVY gh Cdjb Hg ef gPG GdcJGH, hGddg Gdehab ced cJGH s
(3fSNI KGfjI JJab aj BNQgG eY BNQ GdfSNI GdChdis
(3HgG fXGe GdJYbjHIs
(3HgG CKQ JbWjYs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs